Application of chemometrics in combination with Fourier Transform Mid Infrared spectroscopy for authentication of avocado oil - Lumakso, Fajar A.; Riyanto, Sugeng; SA, Shahrel Ahmad; Rosman, Arieff Salleh; Yusoff, Farahwahida Mohd.; Rohman, Abdul (Journal of Food and Pharmaceutical Sciences, 2015)
This recent study was carried out to develop a rapid, simple, and accurate analytical method for authenticity determination of avocado oil (AO). Fourier transform-mid infrared (FT-MIR) spectroscopy technique aided with Partial Least Square (PLS) were optimized for that purpose to binary mixtures of AO with grapeseed oil (GO) and sesame oil (SeO). The calibration models were constructed at following selected MIR region with normal spectra treatment at combination 1006-902; 1191-1091; and 1755-1654 cm-1 (GO in binary mixture with AO) and 4000-650 cm-1 for analysis of SeO in binary mixture with AO. The high value of coefficient of determination (R2) of 0.9994 with low root mean square error of calibration (RMSEC) value of 0.86 %v/v was revealed in GO quantification. Meanwhile, R2 of 0.9997 with RMSEC 0.73 %v/v were obtained for analysis of SeO in binary with AO. The given value of root mean square error of pprediction (RMSEP) during model validation were 0.52 %v/v (GO) and 0.53 %v/v (SeO), respectively. The high value of R2 and low value of RMSEC and RMSEP during calibration and validation were associated with the accuracy and precision of the used method.Â Keywords: avocado oil, FT-MIR spectroscopy, authentication, partial least square.